Utopian social media. Issue 2 (3rd April 2019) - Tosca, Susana
ABSTRACT: Inspired by the work on utopia of Ruth Levitas, and drawing on narrative inquiry and arts-based research methods, this paper presents the result of a series of social media utopia-making workshops where regular users of social media were invited to discuss the things that bother them and propose alternatives to the visions of control and manipulation that fill our reality and the research horizon. The paper is a combination of academic/methodological discourse and creative writing fuelled by the workshop results.